Cabinet of wonders and other Laguna stories - Feleo, Anita B.; Sheniak, David (Manila Published and exclusively distributed by Anvil Pub., 2001)
Travel experience and history of Laguna Province in the Philippines.
Keywords: Laguna -- Description and travel; Laguna -- History